3D Printed Reduced Graphene Oxide/Elastomer Resin Composite with Structural Modulated Sensitivity for Flexible Strain Sensor. Issue 4 (28th October 2021) - Qian, Cheng; Xiao, Ting; Chen, Yang; Wang, Ning; Li, Bo; Gao, Yang
Abstract : High‐performance flexible strain sensors with cost‐effective and scalable fabrication methods are highly demanded for human–machine interfaces, soft robotics, and health monitoring. Herein, a digital light processing‐based 3D printing method, which manufactures structures in a scalable and efficient layer‐by‐layer manner, is developed to prepare a type of flexible strain sensors consisting of reduced graphene oxide/elastomer resin (RGO/ER) composite as the strain sensing element and RGO/ER composite with rhombic structure as the electrode. The RGO/ER composite as the sensing element has a sensitivity of 6.723 at a linear strain detection range from 0.01% to 40% and a high mechanical stability of more than 10 000 stretching–relaxing cycles. Furthermore, through the structural modulation, the sensitivity of the composite responding to mechanical deformation is modulated and suppressed, which can be used as the electrode for the strain sensor. The all‐3D printed device with structurally modulated performance can be used for monitoring various human motions. Abstract : A flexible strain sensor based on reduced graphene oxide/elastomer resin (RGO/ER) composites is developed by digital light processing. The RGO/ER sensing element has a sensitivity of 6.723 at a linear detection range of 40%, while the electrical response of the RGO/ER composite electrode is modulated by the rhombic structures, with an optimized sensitivity of ≈0.815.